The associations between leadership styles and perceived insider status: a meta-analysis - Lin, Yufan; Yang, Yingkai; Shen, Yimo (Frontiers in Psychology, 2025)
The perceived insider status of employees is crucial for the development of both organizations and individuals. This paper provides the first meta-analytic examination of the relationships between leadership styles and followers’ perceived insider status. The meta-analysis examined 12 leadership styles across 137 articles, comprising a total of 151 effect sizes (N = 45,228). The results revealed significant positive correlations between leader-member exchange, differential leadership, inclusive leadership, participative leadership, transformational leadership, empowering leadership, authentic leadership, servant leadership, humble leadership, benevolent leadership, moral leadership, and perceived insider status. Conversely, authoritarian leadership showed a significant negative correlation with perceived insider status. Additionally, the results of relative weight analysis indicated that inclusive leadership exhibited the strongest explanatory power for perceived insider status, while transformational leadership showed the weakest explanatory power. Furthermore, moderation analysis revealed that there were no significant moderation effects of study design, leadership measurement tools, publication status, gender, or age on the relationship between leadership and perceived insider status.